Observed and predicted ages at peak height velocity in soccer players - Malina, Robert M; Coelho-E-Silva, Manuel J; Martinho, Diogo V; Sousa-E-Siva, Paulo; Figueiredo, Antonio J; Cumming, Sean P; Králík, Miroslav; Kozieł, Sławomir M (PLoS One, 2021)
The purpose of the study was to evaluate predicted maturity offset (time before age at PHV) and age at PHV (chronological age [CA] minus maturity offset) in a longitudinal sample of 58 under-13 club level soccer players in central Portugal for whom ages at PHV were estimated with the SITAR model. Two maturity offset prediction equations were applied: the original equation which requires CA sitting height, estimated leg length, height and weight, and a modified equation which requires CA and height. Predicted maturity offset increased, on average, with CA at prediction throughout the age range considered, while variation in predicted maturity offset and ages at PHV within CA groups was considerably reduced compared to variation in observed ages at offset and at PHV. Predicted maturity offset and ages at PHV were consistently later than observed maturity offset and age at PHV among early maturing players, and earlier than observed in late maturing players. Both predicted offset and ages at PHV with the two equations were, on average, later than observed among players maturing on time. Intra-individual variation in predicted ages at PHV with each equation was considerable. The results for soccer players were consistent with similar studies in the general population and two recent longitudinal studies of soccer players. The results question the utility of predicted maturity offset and age at PHV as valid indicators of maturity timing and status.
Keywords: Athletes; Humans; sportovci; Athletic Performance; sportovní výkon; Body Height; Portugal; mužské pohlaví; Age Factors; Soccer; antropometrie; Adolescent; Portugalsko; Anthropometry; Rheology; věkové faktory; reologie; Sexual Maturation; lidé; fotbal; mladiství; dítě; tělesná výška; Child; pohlavní dospělost; Male